Clinical Outcomes and Sturctural Integrity of Rotor Cuff Tears after Arthroscopic Single Row Repair (Journal of Pakistan Orthopaedic Association, 2020)
Aim: To determine the functional and structural outcomes of rotator cuff tears after arthroscopic single row repair with biodegradable suture anchors.Methods: This descriptive study was conducted in Hand & Upper Limb Surgery centre, CMH-Lahore Medical College, Lahore from 3rd January 2016 to 20th August 2019.All patients with rutator cuff tears fulfilling the inclusion criteria were operated arthroscopically with a single row(SR) technique using biodegradable suture anchors. Post operative functional outcomes were assessed at six months follow up with University of California Los Ageles score(UCLA), American Shoulder and Elbow Surgeon score(ASES) and pain assessment with Visual Analogue Scale(VAS).Post operative structural integrity of the rotator cuff was evaluated with ultrasonoghrapic examination. Pearson’s correlation test and Fisher’s exact test were applied to find the significant association between functional outcomes and different demographic variables. P value < 0.05 was considered significant.Results: A total of 40 patients including 36(90%) male and 4(10%) female were included in our study. Mean age at the time of operation was 46.45±13.79 years (range 24-70 years). Right side was involved in 28 (70%) cases and left in 12(30%) patients. Traumatic and degenerative tears were noted in 28(70%) and 12(30%) patients respectively. Mean follow up peroid was 18.1± 6.17 (range 9-31) months. Functional outcomes at final follow up according to UCLA improved from 23.35±7.47 pre operatively to 33.51±1.1 post operatively while ASES score improved from 43.6±4 preoperatively to 70.45±19.87 post operatively.Pre-operative average shoulder pain on VAS was 5.9±0.69 (range 4-8). At last follow up average shoulder pain was 1.95±0.82 range (1-3) with average improvement of 3.95±1.5. Structural integrity on post operative ultrasonoghrapic examination revealed intact rotator cuff in 36 (80%) cases while 8 (20%) cases had re-tear.Conclusion: Arthroscopic single row rotator cuff repair produced excellent functional and structural outcomes and significant pain reduction in majority of our patients. We therefore, recommend this intervention as a suitable treatment option for small to medium size rotator cuff tears.